Trends of unmet need for family planning among currently married reproductive age women in Ethiopia: A multivariate decomposition analysis - Melkalem Mamuye Azanaw; Dawit Tefera Fentie; Yaynemarnesh Asmare Bukayaw; Ayenew Molla Lakew; Malede Mequanent Sisay (Public Library of Science (PLoS), 2022)
Introduction Despite decreasing the percentage of women with unmet needs, Ethiopian women still have a higher unmet need for family planning due to different factors. Therefore, addressing the unmet need for FP provides an opportunity for policymakers in all sectors to respond to the expressed fertility preferences of their population. This study aimed to analyze trends and determinants of changes in unmet needs over time among married women of reproductive age in Ethiopia. Methods The study used data from three consecutive Demographic and Health Surveys conducted in Ethiopia (2005, 2011, and 2016). These nationally representative household surveys cover all Ethiopia region and city administrations with population health and other relevant indicators). The study included a total weighted sample of 8642 in 2005, 10204 in 2011, and 9824 in 2016 in the final analysis. Factors contributing to the change in unmet need rate were examined using logit-based multivariate decomposition analysis. Results Among married women, unmet needs declined from 33.8% (95% confidence interval (CI):32.8,34.8) in 2005 to 21.0%(95%CI:20.2,21.9) in 2016. In decomposition analysis, the difference in coefficients was responsible for 90% of the overall change in the unmet need rate. In particular, being at the age of 25-49 years, rural place of residence, agrarian regions, and having more than four children were significant predictors of the increase in unmet need rate. Conclusions Unmet needs among women have shown a remarkable decline over the last decade in Ethiopia. Policy and program interventions better targeting younger, agrarian regions and rural dwellers would help to maintain a declining trend in unmet needs.